Incorporação de resíduos agrícolas pós-cultivo de cogumelo (SMS) e remineralizador em um argissolo vermelho-amarelo - Araújo, Josefa Vanessa dos Santos (2023)
The population increase and the demand for food has grown exponentially and, consequently, the soils are increasingly exploited, requiring the use of chemical fertilizers to supply the nutrient deficiency. Agronomic residues, both in natura and post-cultivation of mushrooms (SMS), and mining are other environmental problems when accumulated in large proportions and discarded inappropriately. However, the application of these residues has potential when inserted into the soil, allowing, in addition to an adequate destination, the recovery of soils in the process of degradation and the use as natural fertilizers. Thus, the objective of this research was to evaluate whether the residues, both in natura and in SMS, associated with the by-product of the bentonite extraction, improve the chemical properties of the Red-Yellow Argisol. An improvement in the fertility of the studied soil was observed after the incorporation of agronomic residues, in both conditions, in natura and SMS, with the remineralizer. Therefore, in addition to allowing an environmentally appropriate destination for these wastes, their incorporation into a Red-Yellow Argisol contributes to the circular economy and creates more accessible sources of fertilizers.